Kajian Formalisasi PKL di Kawasan Pasar Waru Semarang - Hidayati, Nurani Nurul; Nurini, Nurini (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Formalization of street vendors in the city of Semarang such official site at Waru Market Area in Kaligawe to accommodate that activities. In 2007, the market is prepared to accommodate the relocated Waru merchants of Kartini, Progo and Citarum with klithikan specialities, food of birds and animals. Now, Waru Market conditions have not been developed due to various constraints including accessibility and flooding. Research question of this study is the extent offormalization of street vendors’s rolein Waru Market Semarang. This study utilities was qualitative manner with the purposive sampling methods. The results of this study which is the location of the formalization in the Waru Market area lesssuited to support existing activities. The supply - demand occurred imbalance because services scale market waru still level environment was not compared to demand inflicted. Nevertheless, some traders chose to remain on the grounds selling operating license in accordance with the government so as to provide the most tangible benefits of formalizing the creation of security and comforts for traders. Types of goods and capital will affect the sustainability of the activity of traders, like Klithikan better able to survive in this Waru Market area. Government efforts required as space conditioning goods vendors according to the characteristics and the provision of accessibility to the partnership to be able to support the activities of traders.